Porous nano-HA/collagen/PLLA scaffold containing chitosan microspheres for controlled delivery of synthetic peptide derived from BMP-2 - Niu, X.; Feng, Q.; Wang, M.; Guo, X.; Zheng, Q.
It is advantageous to incorporate controlled growth factor delivery into tissue engineering strategies. The purpose of the present study was to develop a novel tissue engineering scaffold with the capability of controlled releasing BMP-2-derived synthetic peptide. Porous nano-hydroxyapatite/collagen/poly(L-lactic acid)/chitosan microspheres (nHAC/PLLA/CMs)composite scaffolds containing different quantities of chitosan microspheres (CMs)were prepared by a thermally induced phase separation method. Dioxane was used as the solvent for PLLA. Introduction of less than 30
Keywords: POLY(L-LACTIC ACID); CHITOSAN; NANO-HYDROXYAPATITE/COLLAGEN (NHAC); SYNTHETIC PEPTIDE; TISSUE ENGINEERING; CONTROLLED DELIVERY